2019
DOI: 10.1080/15384101.2019.1601477
|View full text |Cite
|
Sign up to set email alerts
|

circ-BIRC6, a circular RNA, promotes hepatocellular carcinoma progression by targeting the miR-3918/Bcl2 axis

Abstract: Circular (circ)RNA is a special type of endogenous RNA consisting of a covalently closed loop structure without 5' to 3' polarity and a polyadenylated tail. Accumulating evidence suggests that circRNAs play important roles in the development and progression of human cancers. However, the role of circRNAs in the progression of hepatocellular carcinoma (HCC) is largely unknown. This was addressed in the present study using high-throughput sequencing to identify aberrantly expressed circRNAs in HCC patient tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…A previous study showed that circ-BIRC6 was highly expressed in HCC tissues and cells, and circ-BIRC6 knockdown inhibited the progression of HCC via regulating the miR-3918/ Bcl2 axis. 13 Moreover, miR-877-5p was reported to be downregulated and play an anti-cancer role in many cancers, such as cervical cancer, 31 glioblastoma, 32 renal cell carcinoma, 33 and colorectal cancer, 34 as well as HCC. 17 In agreement with these findings, we also observed that circ-BIRC6 expression was enhanced, and the miR-877-5p level was reduced in HCC tissue samples and cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that circ-BIRC6 was highly expressed in HCC tissues and cells, and circ-BIRC6 knockdown inhibited the progression of HCC via regulating the miR-3918/ Bcl2 axis. 13 Moreover, miR-877-5p was reported to be downregulated and play an anti-cancer role in many cancers, such as cervical cancer, 31 glioblastoma, 32 renal cell carcinoma, 33 and colorectal cancer, 34 as well as HCC. 17 In agreement with these findings, we also observed that circ-BIRC6 expression was enhanced, and the miR-877-5p level was reduced in HCC tissue samples and cells.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA baculoviral IAP repeat-containing 6 (circ-BIRC6; ID: hsa_circ_0003288, chr2:32,703,702-32,718,734) has been found to act as an oncogene in HCC. 13 However, more functions of circ-BIRC6 and its association with paclitaxel in HCC are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, circ-BIRC6 (ID hsa_ circ_0003288) is located on chromosome 2 (32703702-32718734) and is generated by back-splicing of the BIRC6 transcript (NM_016252). It has been reported that levels of circ-BIRC6 are upregulated in hepatocellular carcinoma (HCC), and depletion of circ-BIRC6 could suppress cell growth, migration, and invasion, representing a potential prognostic factor and therapeutic target for HCC (8). As is well acknowledged, circRNAs regulate gene expression at the transcriptional or posttranscriptional level by binding to microRNAs (miRNAs) or other molecules (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…As is well acknowledged, circRNAs regulate gene expression at the transcriptional or posttranscriptional level by binding to microRNAs (miRNAs) or other molecules (9,10). Mechanically, circ-BIRC6 is reported to function as an oncogenic gene via sponging miR-3918 in HCC (8). Although a close relationship between circRNAs and NSCLC has been reported, the continuous loop which have no 5'-3' polarity and contain no polyA tail.…”
Section: Introductionmentioning
confidence: 99%
“…With the discovery of new circRNAs and the gradual recognition of their functions, the role of circRNAs in tumor pathogenesis and drug resistance has become a hot topic in the eld of tumor research [11]. Studies have shown that circBIRC6 is expressed in a variety of malignant tumors, and can regulate the biological processes of related tumors, such as liver cancer [12]. However, its effect on cisplatin resistance in tumor cells has not been reported.…”
Section: Introductionmentioning
confidence: 99%